Cybernetic Avatar - Ishiguro, Hiroshi; Ueno, Fuki.; Tachibana, Eiki.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book presents a vision of a future, where avatars play an integral role in shaping the fabric of our interconnected society. The book introduces the authors$1 (Bongoing efforts to advance avatar technologies and is structured into nine chapters. Chapter 1 discusses the potentially revolutionary impact of cybernetic avatars (CAs) as a new medium of communication, liberating individuals from physical barriers and creating more flexible work environments. Chapters 2, 3, and 4 present developments in CAs with advanced autonomous functionality. Chapters 5 and 6 discuss the creation of a CA platform that connects multiple operators and CAs. Chapter 7 explores the physiological and neuroscientific effects of avatars and other media on operators and users. Finally, Chapters 8 and 9 discuss the societal implementation of CAs. This book is stemmed from one of the Moonshot R&D projects funded by the Japan Science and Technology Agency (JST).s
1. Introduction Cybernetic Avatar -- 2. Development of Cybernetic Avatars with Human like Presence and Lifelikeness -- 3. Spoken Dialogue Technology for Semi autonomous Cybernetic Avatars -- 4. Human level knowledge and concept acquisition -- 5. Cooperative control of multiple CAs.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Robotics; User Interfaces and Human Computer Interaction; Robotics